(untitled) (Journal of the College of Basic Education, 2022)
In this study, three plant extracts of the following plants were used: Thymus vulgaris, Punica grantum and Quercus robur.The results showed a significant effect of the aqueous and alcoholic extract of peat on the cysts of the parasite compared to the other two plants, followed by the aqueous and alcoholic extract of pomegranate tanner, and finally the aqueous and alcoholic extract of wild thyme.